OPTIMALISASI PENYETELAN CELAH KATUP TERHADAP TEKANAN KOMPRESI PADA KENDARAAN ISUZU PHANTER - Suhendro Oktosatrio; Sugihandoko; Taufan TjandraKusuma (PPM Sdirjianbang Akademi Militer, 2025)
This study aims to determine the effect of valve clearance adjustment on compression pressure and fuel consumption in the Isuzu Panther Bravo vehicle. The background of this research is based on the frequent inaccuracies in valve clearance adjustments caused by the improper use of measuring tools, such as using paper instead of a proper fuller gauge. Incorrect valve clearance settings can lead to various engine problems. When the valve clearance is too tight, the compression pressure becomes low, the engine overheats easily, fuel consumption increases, engine power decreases, and the engine becomes difficult to start. Conversely, if the valve clearance is too wide, the compression pressure also decreases, engine power is reduced, and a knocking or “ticking” sound appears when the engine is running. The research was conducted using nine different valve clearance settings, both for the intake and exhaust valves, ranging from 0.20 mm to 0.60 mm. Each variation was tested using a compression pressure gauge to measure the resulting pressure for each setting. The test results showed varying but relatively close values, so an average was calculated to determine the most ideal valve clearance. The findings of this study are expected to provide practical guidance in setting the correct valve clearance to achieve optimal compression pressure and maximum fuel efficiency in the Isuzu Panther Bravo engine. Moreover, it emphasizes the importance of using the proper measuring instrument, such as a fuller gauge, to ensure accuracy in valve clearance adjustments. Keywords: valve clearance, compression pressure, engine efficiency, Isuzu Panther , optimization